2009
DOI: 10.1029/2009gl041037
|View full text |Cite
|
Sign up to set email alerts
|

Optical and particle observations of type B red aurora

Abstract: Aurora occasionally exhibits short‐lived appearance of a bright red border at the bottom of an auroral arc, band, or curtain. This is called a type B red aurora. Based on simultaneous measurements of auroral emissions from N2 1PG (“red” aurora) and O (1S) (“green” aurora) as well as incident electrons by the Reimei satellite, we show the following two individual observations. Energy flux and average energy of incident electrons (1) were not always higher in the red‐dominated aurora than in the green‐dominated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…Hereinafter we call this a smokelike aurora. The field of view of MAC was rather small (∼70 × 70 km) and the satellite moved rapidly, so that MAC could not keep observing the same part of the aurora more than ∼9 s. We confirm that the smokelike auroras maintained their shape at least for ∼9 s. That is, the smokelike aurora is clearly distinguished from the discrete, active aurora observed by Reimei/MAC [ Obuchi et al , 2008; Ebihara et al , 2009], pulsating aurora [ Røyrvik and Davis , 1977], and black aurora [ Davis , 1978].…”
Section: Data Presentationsupporting
confidence: 60%
“…Hereinafter we call this a smokelike aurora. The field of view of MAC was rather small (∼70 × 70 km) and the satellite moved rapidly, so that MAC could not keep observing the same part of the aurora more than ∼9 s. We confirm that the smokelike auroras maintained their shape at least for ∼9 s. That is, the smokelike aurora is clearly distinguished from the discrete, active aurora observed by Reimei/MAC [ Obuchi et al , 2008; Ebihara et al , 2009], pulsating aurora [ Røyrvik and Davis , 1977], and black aurora [ Davis , 1978].…”
Section: Data Presentationsupporting
confidence: 60%
“…Narrow rays are known to exhibit a violet colour at the leading edge and a green colour behind owing to the lifetime of O( 1 S) being longer than that of excited N 2 + (Omholt, 1971, p. 126). The delay of the 557.7 nm [OI] emission is confirmed by simultaneous observations of aurora and precipitating electrons (Ebihara et al ., 2009). The pinkish or bluish colouration extending to higher altitudes is also attributed to nitrogen emissions (N 2 + ) in sunlit aurorae (Hunten, 2006; Shiokawa et al ., 2019).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Highly rapid variations of the different types of auroral forms represented by curtains, rays, and vortices have been observed by a new type of simultaneous observations of both auroral imaging and in situ particle measurements made by high-time/spatial resolutions of the instruments on the Reimei satellite (Asamura et al, 2003;Sakanoi et al, 2003). Owing to the simultaneous image-particle observations with the high resolutions, Ebihara et al (2009) successfully derived a novel interpretation concerning the reddening of auroral arcs. Asamura et al (2009) and Saito et al (2011) reported a case study based on fine-scale observations of the auroral forms and particles for addressing the significance of the Alfvénic electron acceleration in the auroral arcs.…”
Section: Reimei Observations With High Resolutionsmentioning
confidence: 99%
“…Owing to the simultaneous image‐particle observations with the high resolutions, Ebihara et al. (2009) successfully derived a novel interpretation concerning the reddening of auroral arcs. Asamura et al.…”
Section: Introductionmentioning
confidence: 99%